A regression analysis: ergonomic comfort vs. air quality, noise, lighting and temperature in the composite trimming process working room / Azurin Shukur …[et al.] - Shukur, Azurin; Hussein, N.I.S; Kama, S.R.; Yuniawan, D. (Universiti Teknologi MARA, 2021)
This study was set to identify how working environment affected workers’ comfort and to determine the maximum level of air quality, noise, lighting and temperature allowed for each working environment. Workers seemed uncomfortable with the working environment in the working room. To validate the situation, a survey was conducted in the present study on all workers who were involved in the cutting process to determine their feelings in certain setting environment conditions. Next, the environment values were obtained by using specific and certain measurement tools. All the data taken from these two conditions were analyzed using the Minitab software. The study found that most of the working environment parameters in the trimming room exceeded the maximum allowable level of ISO standards. For air quality an average of 30% RH was obtained, which was below the allowable value of 40 – 60% RH. For noise, the obtained value was about 150 dB, which exceeded the maximum level of 85 dB. For in-room lighting, the obtained value was about 200 lux; far below the ISO standard of 750 lux and finally, for temperature the obtained value was about 31.70C, which was higher than ISO standard of 260C. It can be concluded that all the working environments do not contribute to good feeling to the workers while doing their job in that room. This means that measures need to be taken to overcome the situation in order to improve the workers’ feelings and provide them with comfort while doing their job.